Sistem Rekomendasi untuk Mahasiswa Mendaftar sebagai Panitia ke dalam Acara Menggunakan Metode Content-Based Recommendation Systems - Daniel Valentino Hidayat; Justinus Andjarwirawan; Leo Willyanto Santoso (Jurnal Infra, 2019)
In this day, technology is needed in doing many things that can make it easier for humans to carry out their activities. but there are still many things that are still being done manually and that is less effective. Especially in terms of registering as a member in an event at the Petra Christian University. The purpose of this paper is to create a registration system into an event to help students who need organizational credit points and make it easier for an organization to receive its members.The method that will be used is Content-based recommendation systems, which is a system recommendation method that uses data about each product to recommend new products. In making this application will use student data and data about an activity so that the system recommends division to students in accordance with the division that has been followed by a student from previous events.In this paper a website will be created using the Laravel framework and the database using MySQL.Based on the results of the questionnaire it can be concluded that registering as a member using a system created by the author is more effective than registering manually. And when the organizers of the organization will choose which students will be accepted, this will benefit final level students because the list of registrants is sorted by the year the student enters.